Ex-Situ Conservation of Landsnail Asperitas trochus penidae and its unique life - suryadinata suryadinata; Sunarjo Leman (Jurnal Moluska Indonesia, 2022)
Conservation is one of the efforts to preserve the survival of animals whose population is likely to decrease or are threatened with extinction. Land snails of certain species are increasingly being found in the wild or in their natural habitat due to the decreasing condition of natural locations and also due to the rapid development of urban areas both for settlements and other infrastructure. Many certain species are no longer found in nature and may have become extinct. One way to preserve the life of land snails is to try to do conservation outside their natural habitat and find unique behavior that have not been revealed in research in their natural habitats. The research method was to conduct qualitative and quantitative observations by collecting data and observing 4 Asperitas trochus penidae which were kept in glass cages for more than a year and continued in open cages. During the research, it was found that Asperitas trochus penidae can live healthy in an open and artificial glass cage and can reproduce even if they are fed non-natural or artificial food. There are several important things to be learned during ex-situ conservation such as behavior during feeding, breeding and uniqueness that are missed when conducting research in the wild.